Multimodal interactions in a carbonated beverage system - Hewson, Emma Louise (2008)
Predicting flavour perception is complicated by interactions occurring both within and across sensory modalities, but understanding these interactions and the resulting multimodal integration is crucial to the formulation of successful products. Despite the commercial appeal of carbonated soft drinks, few studies have examined the effects of tastant: aroma: carbonation interactions on sensory perception.